Analisa Tentang Kebijakan Moneter Islam dan Pendapatan Negara Terhadap Pertumbuhan Ekonomi - Nuri Alvin; Revalina Melati Ayuningtyas; Yustris Baldwin Khadafi (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
This research analyzes Islamic monetary policy and state revenues in the context of economic growth, especially in Indonesia. Monetary policy is the government's effort to improve economic conditions by regulating the amount of money in circulation. In the context of an economic crisis, monetary policy becomes important to balance the real sector and overcome the problem of currency value and the role of money as a commodity that sells interest or usury. This research reveals that monetary policy has input in the form of monetary policy instruments that influence the amount of money in circulation, while the output includes price stability and economic output. Islamic monetary policy is emphasized as a policy that must be free from usury and interest, following the principle of profit sharing in money management. Apart from that, this research also reviews monetary policy during the time of Rasulullah SAW, where monetary management was based on the principle of baitul mal and the allocation of funds for the spread of Islam, education, infrastructure development and social welfare. an Islamic economic perspective, monetary policy must pay attention to economic welfare with full employment opportunities, socio-economic justice, income distribution, and stability of the value of money. This refers to the principles of maqasid sharia in creating balance and prosperity for society. Monetary policy in Indonesia, led by Bank Indonesia, uses various instruments such as reference interest rates, open market operations, provision of liquidity, regulation of storage facilities, and reserve requirements. mandatory to achieve price stability, economic growth and financial system stability. This research provides in-depth insight into the importance of Islamic monetary policy in achieving macroeconomic goals and its impact on economic growth in Indonesia.